A digital model of a stream-aquifer system on the South Platte River near Sterling, Colorado - Olson, Alan F., author; Longenbaugh, R. A., advisor; Sunada, D. K., committee member; McWhorter, D. B., committee member (Colorado State University. Libraries, 1973)
A digital finite difference groundwater model was developed for a stream-aquifer system in northeastern Colorado. The general mathematical model and computer program used in the study were developed by the Groundwater staff at Colorado State University. The model uses a finite difference approximation of the basic non-linear equation describing transient flow in a saturated porous media. The twenty square mile study area includes a nine mile reach of the South Platte River and a portion of Prewitt Reservoir. Simulated water table elevations were compared with historic water level data for the period of November, 1969 to November, 1971. A satisfactory match of simulated and historic water table elevations was obtained for the second year of analysis. Due to inadequate data on the existing aquifer conditions near the reservoir, problems were encountered in simulating the monthly reservoir seepage. As a result, use of the model is limited to certain conditions of reservoir storage.
Keywords: Groundwater -- South Platte River (Colo. and Neb.) -- Mathematical models; Groundwater -- Colorado -- Logan County -- Mathematical models